The effects of intersectional stigma and discrimination on the mental well-being of Black, LBQ, female youth 18–25 years old - Richards, Donna; Gateri, Hellen; Massaquoi, Notisha (My University, 2018)
This chapter focuses on Black, lesbian, bisexual, and queer female youth and the effects of intersectional stigma on their mental well-being. Labels such as "lesbian", "bisexual", and "queer" are used to refer to women who have same-sex desires. Few studies addresses the intersectional stigma that Black, lesbian, bisexual, and queer (LBQ) female youth face in a society where racism, sexual orientation, and homophobia intersect with other social inequities. Throughout the chapter, in addition to LBQ, the acronyms LGBTQ (lesbian, gay, bisexual, transgender, and queer) and LGBQ are used because much of the literature reviewed concerns the larger LGBTQ community. It found that this group not only experiences discrimination in society in general, but may also face discrimination within the LGBTQ communities. Oftentimes, they also face rejection or pressure to remain closeted in their own racial/ethnic communities because of heteronormative cultural pressures. It purposely excludes transgendered populations as one's social work practice experiences have been primarily with the LBQ population. Transgender is an umbrella term used to refer to identities such as transgender and intersex.
Keywords: female youth; Black; lesbian; queer; intersectional stigma